2016
DOI: 10.1590/1982-0194201600072
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados à qualidade de vida de pacientes renais crônicos em hemodiálise

Abstract: Objective: To identify sociodemographic and clinical factors associated with health-related quality of life of patients with chronic kidney disease on hemodialysis. Methods: This was a descriptive, cross-sectional, quantitative study conducted with 101 patients with chronic kidney disease on hemodialysis. An instrument for subject characteristics, and the Kidney Disease and Quality of Life -Short Form were used. For multivariate analysis, logistic regression with Stepwise selection criteria variables was used.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 12 publications
1
5
0
14
Order By: Relevance
“…and HRQoL in CKD is well established (8)(9) , it can be deepened with respect to the commitment of each domain that integrates it. Studies with chronic renal patients undergoing hemodialysis have also shown an association between quality of life, sociodemographic characteristics (10)(11)(12) and comorbidities (13) . Regarding the relationship with complications of kidney disease, few studies have attempted to identify it (14) or assess association with specific complications, such as pain (15) and anemia (16) .…”
Section: Although the Relationship Between Depressionmentioning
confidence: 99%
“…and HRQoL in CKD is well established (8)(9) , it can be deepened with respect to the commitment of each domain that integrates it. Studies with chronic renal patients undergoing hemodialysis have also shown an association between quality of life, sociodemographic characteristics (10)(11)(12) and comorbidities (13) . Regarding the relationship with complications of kidney disease, few studies have attempted to identify it (14) or assess association with specific complications, such as pain (15) and anemia (16) .…”
Section: Although the Relationship Between Depressionmentioning
confidence: 99%
“…A função dos rins pode ser avaliada pela filtração glomerular (FG) e a sua diminuição é observada na Insuficiência Renal Crônica (IRC), que é associada à perda das funções regulatórias, excretórias e endócrinas do rim (FUKUSHIMA et al, 2016). Quando a FG chega a valores muito baixos, inferiores a 15 ml/m, é determinado o que se denomina de falência funcional renal (FFR), ou seja, é considerado o estágio mais avançado da perda funcional progressiva, percebido na IRC (BASTOS et al, 2010).…”
Section: Resultsunclassified
“…A relevância da religião pauta-se no dado de que pacientes hemodialítico praticantes de alguma religião apresentaram melhor qualidade de vida em relação àqueles que não apresentam crença religiosa (22) . Outro estudo (23) , que analisou as atitudes religiosas de pessoas em tratamento hemodiálitico, apontou que pacientes que tinham menos conhecimento religioso tinham maior facilidade em aderir ao tratamento.…”
Section: Discussionunclassified